PHENOMENA INTRUSI DASAR DI TELUK HURUN LAMPUNG - Santoso, Arif Dwi (Jurnal Air Indonesia, 2007)
Research aimed to learn and know the bottom intrusion mechanism in Hurun Bay Lampung. Three kinds surveys were conducted consist of mooring survey, synoptic oceanographic survey and 25 hour survey. The monitoring data of water temperature indicated that at Hurun Bay occurred bottom intrusion from middle February until early July. The mass water was colder, more saline and contained less DO than the overlaying water. These phenomena may be caused by eastern monsoon from Java Sea to Lampung Bay and Hurun Bay. Vertical profile distribution showed that there are significant different in temperature, salinity and DO between surface and bottom layer. Along bottom deeper than 22m were identified as a termocline layer which was colder and more saline and contained less DO. Result of 25 hour survey resumed that the lowest DO in this water mass appeared in early July and it propagated from offshore to the coast with velocity 0.07 m/s. This condition will be a treatment for marine cultivation stakeholder in this area.Key words : Bottom Intrusion, Hypoxia